Genome-resolved metagenomics reveals role of iron metabolism in drought-induced rhizosphere microbiome dynamics - Ling Xu (Nature Portfolio, 2021)
Advances in omics provide a tool to understand mechanisms for plant–microbial interactions under stress. Here the authors apply genome-resolved metagenomics to investigate sorghum and its microbiome responses to drought, identifying an unexpected role of iron metabolism.